PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KETERAMPILAN MENULIS TEKS CERITA MORAL/FABEL SISWA KELAS VIII SMP NEGERI 4 SOLOK SELATAN - Ena Noveria, Rosi Nur Akbar Utami, Ermawati Arief, (Universitas Negeri Padang, 2017)
There are three purposes of this research. First, to know writing skill level of moral / fable story before using cooperative learning model think pair share. Second, to know writing skill level of moral/ fable by using cooperative learning model of think pair share. Third, describe the influence of the use cooperative learning model of think pair share toward writing skill of moral/fable story text. The type of the research is quantitative with quasi-experimental methods. It was concluded that the moral / fable story writing skill after using cooperative learning model of think pair share is better than before using cooperative learning model of think pair share.Â Kata kunci: pengaruh, think pair share, menulis teks cerita moral/fabel